3D Finite Elements Modelling for Design and Performance Analysis of UO2 Pellets. (8th February 2011) - Demarco, Gustavo L.; Marino, Armando C.
Abstract : The geometry of a fuel pellet is a compromise among the intention to maximize UO2 content and minimize the temperature gradient taking into account the thermomechanical behaviour, the economy, and the safety of the fuel management during and after irradiation. "Dishings", "shoulders", "chamfers", and/or "a central hole" on a cylinder with an improved l/d relation (length of the pellet/diameter) are introduced in order to optimize the shape of the pellet. The MeCom tools coupled with the BaCo code constitutes a complete system for the 3D analysis of the stress strain state of the pellet under irradiation. CANDU and PHWR MOX fuel will be used to illustrate the excellent qualitative agreement between experimental data and calculations by using these computational tools.